1990
DOI: 10.1139/m90-105
|View full text |Cite
|
Sign up to set email alerts
|

Current status of Azospirillum inoculation technology: Azospirillum as a challenge for agriculture

Abstract: The genus Azospirillum The first species of Azospirillum was isolated by Beijerinck (1925) from N-poor sandy soil in the Netherlands and was originally named Spirillum lipoferum. This bacterium was later isolated from soil (Schroder 1932

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0
13

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(211 citation statements)
references
References 223 publications
6
187
0
13
Order By: Relevance
“…Hormonal effects, however, are complex and, often, specific responses result not from a single hormone but from the balance of several (28). Other investigators have encountered similar difficulties in demonstrating hormonal regulation or production as a mechanism of growth promotion, and the evidence remains mostly circumstantial (3,7,14,23). Our approach for studying growth promotion is to produce nonpromoting mutants (isogenic to the parental strain) by Tn5 transposon mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal effects, however, are complex and, often, specific responses result not from a single hormone but from the balance of several (28). Other investigators have encountered similar difficulties in demonstrating hormonal regulation or production as a mechanism of growth promotion, and the evidence remains mostly circumstantial (3,7,14,23). Our approach for studying growth promotion is to produce nonpromoting mutants (isogenic to the parental strain) by Tn5 transposon mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PGPR with ACC deaminase were isolated from rhizosphere of various plants (Belimov et al, 2001). What's more, some rhizobacteria can promote plant growth by the synthesis of other compounds, such as siderophores, indole-3-acetic acid (IAA) and antibiotics with heavy metal contaminants, which is different from organic pollutants (Burd et al, 2000;Glick, 2001;Pattern and Glick, 1996) or though stimulation of certain metabolic pathways such as nitrogen fixation and the uptake of nitrogen, phosphorus, S, Mg, Ca and other nutrients (Bashan and Levanony, 1990;Belimov and Dietz, 2000;Okon and Labandera-Gonzalez, (2003) 1994). Leong (1986) reported that heavy metals in soils could stimulate the production of siderophores.…”
Section: Prompting Plant Growthmentioning
confidence: 99%
“…The similar results between the inoculation of the strains associated with the N fertilizations of 30 kg ha -1 and 160 kg ha -1 reflect the effect of growth promotion caused by the PGPB, involving a set of mechanisms besides the production of phytohormones, such as biological control of phytopathogens, BNF and solubilization of phosphates (Bashan & Levanony, 1990;Pidello et al, 1993). In addition, the inoculation of PGPB associated with low N doses has shown greater efficiency for the plant-bacteria system, in comparison to isolated inoculation, while the application of high N doses reduces such efficiency due to the plant response to the stimulation in the absorption of the nutrient, limiting the biological process (Bárbaro et al, 2008).…”
Section: Resultsmentioning
confidence: 64%